![image](https://tex.z-dn.net/?f=%283x%2Bx%5E2%29%20%5E2-x%5E2%20%28x-5%29%20%28x%2B5%29%20-2x%20%288-3x%5E2%29%20%3D%20%20%5C%5C%20%20%3D%209%20%7Bx%7D%5E%7B2%7D%20%20%2B%206%20%7Bx%7D%5E%7B3%7D%20%20%2B%20%20%7Bx%7D%5E%7B4%7D%20%20-%20%20%7Bx%7D%5E%7B2%7D%20%28%7Bx%7D%5E%7B2%7D%20%20-%2025%29%20-%2016x%20%2B%206%20%7Bx%7D%5E%7B3%7D%20%20%3D%20%20%5C%5C%20%20%3D%209%20%7Bx%7D%5E%7B2%7D%20%20%2B%206%20%7Bx%7D%5E%7B3%7D%20%20%2B%20%20%7Bx%7D%5E%7B4%7D%20%20-%20%20%7Bx%7D%5E%7B4%7D%20%2B%20%2025%20%7Bx%7D%5E%7B2%7D%20%20-%2016x%20%2B%206%20%7Bx%7D%5E%7B3%7D%20%3D%20%20%20%5C%5C%20%20%3D%2012%20%7Bx%7D%5E%7B3%7D%20%20%2B%2034%20%7Bx%7D%5E%7B2%7D%20%20-%2016x%3C%2Fp%3E%3Cp%3E)
" alt="(3x+x^2) ^2-x^2 (x-5) (x+5) -2x (8-3x^2) = \\ = 9 {x}^{2} + 6 {x}^{3} + {x}^{4} - {x}^{2} ({x}^{2} - 25) - 16x + 6 {x}^{3} = \\ = 9 {x}^{2} + 6 {x}^{3} + {x}^{4} - {x}^{4} + 25 {x}^{2} - 16x + 6 {x}^{3} = \\ = 12 {x}^{3} + 34 {x}^{2} - 16x
" align="absmiddle" class="latex-formula">